New records for the Middle Siwalik flora of eastern Nepal and their climatic significance - Purushottam Adhikari; Lalit K. Rai; Sadanand; Harshita Bhatia; Gaurav Srivastava; Niraj Singh Thakuri; R.C. Mehrotra; Khum N. Paudayal (Earth History and Biodiversity)
The Siwalik plant fossils are important in understanding the climate change caused by the uplift of the Himalaya. The plant fossil assemblages are abundantly known from Nepal's central and western Siwalik sediments. However, they are poorly known from the Siwalik of the eastern region from where the modern Indian Summer Monsoon (ISM) enters Nepal. That is why fossils of this region are important in understanding the evolutionary history of ISM in Nepal. In the present communication, we report four new fossil leaf impressions/ compressions, namely Thelypteridaceophyllum tertiarum Joshi and Mehrotra of the family Thelypteridaceae, Calophyllum suraikholaensis Awasthi and Prasad of the Calophyllaceae, Albizia siwalica Prasad of the family Fabaceae, and Daphnogene makumensis Mehrotra, Dilcher et Lott of the family Lauraceae from the well-dated Middle Siwalik (∼9.5 Ma) sediments of eastern Nepal. The aforementioned and previous fossil records suggest that seasonal or monsoonal rainfall was present during the deposition of the sediments.